Interleukin-1 gene polymorphisms and their relation with NFkB expression and histopathological features in psoriasis - Nikhil Moorchung; Biju Vasudevan; Manas Chatterjee; N S Mani; R S Grewal (Wolters Kluwer Medknow Publications, 2015)
Background: Psoriasis is a chronic inflammatory disease driven by exaggerated production of pro-inflammatory cytokines and interleukins. Various genetic polymorphisms including IL-1 are implicated in pathogenesis of psoriasis. The exact role of IL-1 gene polymorphisms and their interaction with NFκB is not yet determined. We aimed to study various genetic polymorphisms of IL-1 in psoriasis and their influence on NFκB and histopathological features. Materials and Methods: 112 newly diagnosed cases of psoriasis vulgaris were included in this prospective study. Histology was done on sections and genotyping was done for the IL-1β and IL-1 receptor antagonist (IL-1RA) genetic polymorphisms. In addition, NFκB immunostaining was performed on 89 sections and the intensity of staining was evaluated in the epidermis, basal cells, and the lymphocytes. Results : A strong association of IL-1β 511 C/T polymorphism was found with both genotypes and alleles in psoriasis. A strong correlation was also detected between the IL-1β genotype and the grade of NFκB immunostaining in the epidermis (P = 0.012). The grade of NFκB lymphocyte staining showed a strong correlation with the IL-1RA genotype (P = 0.025) but not with the IL-1β genotype (P = 0.226). The genetic polymorphisms did not show any correlation with the histological features. Conclusions: IL-1 genetic polymorphisms may not play a very direct role in pathogenesis of psoriasis. However, their interaction with NFκB appears to be a significant factor in this direction as NFκB is activated by pro-inflammatory genetic polymorphisms and therefore may influence the severity of psoriasis.